Is Intuitive Eating a Mediator Between Stress and Adiposity in Midlife Women?. (14th June 2022) - Owens, Bridget; Oaks, Brietta; Sabik, Natalie; Tovar, Alison; Ward-Ritacco, Christie
Abstract: Objectives: Stress increases appetite for highly palatable foods and can affect decision-making. Thus, higher stress may interfere with the ability to eat intuitively and result in calorie intake that exceeds physiological needs, contributing to increased adiposity. To our knowledge this relationship has not been explored. Our objective was to examine the association between perceived stress and adiposity in midlife women and test whether intuitive eating (IE) mediates this relationship. Methods: Data from a cross-sectional study of midlife women, 40–64 years of age (n = 113), conducted April 2017 to July 2019 was analyzed. Participants completed two in-person visits and self-reported questionnaires, including the Perceived Stress Scale and the Intuitive Eating Scale. Adiposity was assessed by dual energy x-ray absorptiometry. We examined the following subscales of the Intuitive Eating Scale as possible mediators: 1) unconditional permission to eat, 2) eating for physical rather than emotional reasons, and 3) reliance on internal hunger and satiety cues. We used structural equation modeling and bootstrap confidence intervals to examine mediation of intuitive eating through perceived stress and adiposity. Results: The direct path from perceived stress to adiposity was not significant (Β = 0.07, p = .51) and indirect effects through the intuitive eating subscales were not significant. Higher perceived stress was associated with both lower reliance on internal hunger and satiety cues (Β = −0.02, p = .04) and lower eating for physical reasons (Β = −0.04, p = .003), and lower reliance on internal hunger and satiety cues was associated with higher adiposity (Β = −5.49, p < .01). Eating for physical reasons was not associated with adiposity (Β = −1.38, p = .12) and unconditional permission to eat was not associated with perceived stress (Β = −0.006, p = .59) or adiposity (Β = 0.55, p = .63). Conclusions: Though mediation was not present, lower reliance on hunger and satiety cues was independently associated with higher perceived stress and higher adiposity in this sample of midlife women. Given the association between higher perceived stress and lower intuitive eating, future research is warranted to examine possible physiological reasons explaining this relationship. Funding Sources: Supported by funds from the College of Health Sciences at the University of Rhode Island.